Inductive limits of increasing-sequences of commutative topological groups. (I) - Karklinš, J. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. В. Карклиньш. Индуктивные пределы возрастающих последовательностей коммутативных топологических групп. (I) J. Karklinš. Komutatyvinių topologinių grupių didėjančių sekų induktyvinės ribos. (I)